2006
DOI: 10.1590/s0036-46652006000600008
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of neurocysticercosis in patients with epileptic seizure using ELISA and immunoblot assay

Abstract: SUMMARYSera from 88 patients from Santa Catarina and São Paulo states of Brazil, with epileptic seizures who underwent cerebral computed tomography (CT) were analyzed for the detection of antibodies to T. solium cysticercus by ELISA and Immunoblot (IB) with the following antigens: Taenia solium cysticercus total saline (Tso), Taenia crassiceps cysticercus vesicular fluid (Tcra-vf) and T. crassiceps cysticercus glycoproteins (Tcra-gp). ELISA carried out with Tso, Tcra-vf and Tcra-gp antigens showed 95%, 90% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
(23 reference statements)
0
13
0
1
Order By: Relevance
“…Prestes-Carneiro et al (2006) evaluated cysticercosis occurrence in peasant's settlement inhabitants in the state of São Paulo and found 3.6% of infected humans. In addition, neurocysticercosis is the major cause of epileptic seizure in Brazil (Ishida et al 2006). This study evaluated animal samples from peasant's settlements, reinforcing the appeal for health authorities to improve basic sanitation at rural communities, aiming on reducing treatment costs and promoting public health in these populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prestes-Carneiro et al (2006) evaluated cysticercosis occurrence in peasant's settlement inhabitants in the state of São Paulo and found 3.6% of infected humans. In addition, neurocysticercosis is the major cause of epileptic seizure in Brazil (Ishida et al 2006). This study evaluated animal samples from peasant's settlements, reinforcing the appeal for health authorities to improve basic sanitation at rural communities, aiming on reducing treatment costs and promoting public health in these populations.…”
Section: Resultsmentioning
confidence: 99%
“…The ingestion of water or food contaminated with the parasite's eggs are the main infection pathway of human cysticercosis. In the event of eggs ingestion, neurocysticercosis commonly occurs and is considered one of the most important diseases in Latin America (Flisser et al 2003) and the major cause of epileptic seizures in Brazil (Ishida et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In 107 patients with solitary cysticercus granuloma, the ELISA and immunoblot were positive in 80% and 62% of the cases, respectively, whereas in non-cysticercosis patients, the ELISA and immunoblot were negative in 94% and 97% of the cases, respectively. Ishida et al 30 evaluated the performances of different cysticercal antigens (T. solium cysticercal total saline, Tso; T. crassiceps cysticercal vesicular fluid, Tcra-vf and T. crassiceps cysticercal glycoproteins, Tcra-gp) for the immunodiagnosis of neurocysticercosis using ELISA and immunoblot. In 20 serum samples from patients with neurocysticercosis confirmed by neuroimaging studies, the ELISA done with Tso, Tcravf and Tcra-gp was positive in 19 (95%), 18 (90%) and 16 (80%) patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is very difficult to obtain enough quantities of an antigen as that depends either on finding naturally infected swine or infecting them experimentally with T. solium eggs. Several studies have shown that C. longicollis could replace C. cellulosae because both parasites shared antigenic elements able to be used in ELISA or immunoblottings (Vaz et al, 1996;Bueno et al, 2000;Pardini et al, 2002;Ishida et al, 2006). Therefore, the use of this heterologous antigen may contribute for seroepidemiologic studies to evaluate the complex taeniasis/cysticercosis (Vaz et al, 1996;, Sciutto et al, 2000, Ito, 2000.…”
Section: Discussionmentioning
confidence: 99%